Height Control of Supersonic Sea-Skimming Missiles Based on Online Parameter Identification - Zhenyu Jiang; Xiaobin Tang; Xiaoshuai Fan; Shifeng Zhang (International Journal of Aerospace Engineering)
This paper presents a height control approach employing real-time parameter identification for supersonic sea-skimming missiles. Firstly, an integrated identification technique based on the Unscented Kalman filter was established for supersonic cruise missiles. The method facilitates the online identification of aerodynamic and thrust coefficients while simultaneously estimating state variables such as height and angle of attack. Secondly, a backstepping control method was designed to regulate the height of sea-skimming missiles. Control commands were generated based on online identification and state estimation, as well as the additional angle of attack caused by wind being compensated. The simulation results show that the proposed height control method achieved a high level of precision when operating in the challenging conditions of ultralow-height sea skimming, despite the presence of parameter uncertainties, measurement inaccuracies, sea wave disturbances, and wind effects.